Enzymatic debridement of deeply burned faces: Healing and early scarring based on tissue preservation compared to traditional surgical debridement. Issue 6 (September 2017) - Schulz, Alexandra; Fuchs, Paul Christian; Rothermundt, Irene; Hoffmann, Alexandra; Rosenberg, Lior; Shoham, Yaron; Oberländer, Henrik; Schiefer, Jennifer
Highlights: Scarred healing may cause permanent functional, cosmetic and psychosocial sequelae. Enzymatic debridement assists in burn depth evaluation and tissue preservation. Enzymatic is associated with higher spontaneous epithelialization. Better scar quality after three months with enzymatic debridement. Abstract: Introduction: Facial burns occur frequently and depending on the injured skin layers often heal with scars which may cause permanent functional and cosmetic sequelae. Preservation of the sensitive facial skin layers, especially of the dermis is essential for scarless epithelialisation. Enzymatic debridement of deep thermal burns has already been shown to assist with preserving viable dermis. However, up to date, there are no published reports on wound healing and in the long term aesthetic outcome after enzymatic debridement of facial burns. Methods: Therefore we performed a—single centre clinical trial that included 26 subjects aged 18–78 years with facial burns clinically evaluated as deep dermal or deeper. Burns were treated either with enzymatic debridement or excisional surgical debridement. Then we compared both groups regarding debridement selectivity, wound closure and scar quality after more than 12 months. Results: Enzymatic debridement significantly reduced time to complete wound closure after admission (19.85 days versus 42.23 days, p = 0.002), and after enzymatic eschar removal (18.92 days versus 35.62 days, p = 0.042). The number of procedures to complete debridement were significantly lower in the enzymatic debridement group (1.00 versus 1.77, p = 0.003). 77% of facial burns that had been debrided enzymatically were found to be more superficially burned than initially estimated. Wounds undergoing autografting of any size were significantly reduced by enzymatic debridement (15% versus 77%, p = 0.002). Scar quality after enzymatic debridement was superior compared to surgical debridement after 12 months regarding pigmentation (p = 0.016), thickness (p = 0.16), relief (p = 0.10), pliability (p = 0.01), surface area (p = 0.004), stiffness (p = 0.023), thickness (0.011) and scar irregularity (p = 0.011). Regarding erythema and melanin, viscoelasticity and pliability, trans-epidermal water loss or laser tissue oxygen saturation, haemoglobin level and microcirculation we found no significant differences for treated and untreated skin in the EDNX group. Conclusion: In our current study we found Bromelain based enzymatic debridement better in some aspects of tissue preservation in deep dermal facial burn.